INTERCULTURAL COMMUNICATION BARRIERS FOR COUPLES IN DEPOK CITY - Ahandini Nirmala Sukma; Risma Kartika (Universitas Prof. Dr. Moestopo (Beragama), 2022)
The phenomenon of intercultural marriage is something that is often encountered in Indonesia. The number of islands, cultures, ethnicities, and languages that Indonesia has makes diversity can be found in several aspects of life, one of which is marriage. Communication that occurs in inter-ethnic married couples certainly has several obstacles that can cause miscommunication and lead to conflict in the household. The purpose of this study was to determine the barriers to intercultural communication in married couples in Depok City. The concepts in this study consist of Intercultural Communication and Barriers to Intercultural Communication. This research uses a qualitative approach and descriptive research type. The results of this study were that six of informants each encountered obstacles both above and below the waterline. From the statements of the six informants, it can be concluded that the obstacles that occur are caused by differences in understanding and lack of communication of each individual regarding the categories of intercultural communication barriers above waterline, below waterline and prejudice. In addition, ethnocentrism only occurs in one informants only